2007
DOI: 10.1016/j.yebeh.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, family environment, and behavior problems in children with new-onset seizures

Abstract: Children with epilepsy, even those with new-onset seizures, exhibit relatively high rates of behavior problems. The purpose of this study was to explore the relationships among early temperament, family adaptive resources, and behavior problems in children with new-onset seizures. Our major goal was to test whether family adaptive resources moderated the relationship between early temperament dimensions and current behavior problems in 287 children with new-onset seizures. Two of the three temperament dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Specific temperamental factors have been shown to be risk factors for internalizing and externalizing problems both in healthy children and in children with seizures [13-16]. In an earlier study of the present sample of children with new-onset seizures, 72.6% of whom have epilepsy, we showed that retrospectively-assessed infant temperamental characteristics, such as difficultness (negative emotionality), unadaptability (negative reaction to novelty), and resistance to control (unmanageability) were related to both total and internalizing behavior problems, whereas only difficultness and resistance to control were associated with externalizing behaviors [14]. Although temperament was shown to be predictive of behavior at the time of seizure onset, it is unclear whether it remains predictive years after seizures have developed.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Specific temperamental factors have been shown to be risk factors for internalizing and externalizing problems both in healthy children and in children with seizures [13-16]. In an earlier study of the present sample of children with new-onset seizures, 72.6% of whom have epilepsy, we showed that retrospectively-assessed infant temperamental characteristics, such as difficultness (negative emotionality), unadaptability (negative reaction to novelty), and resistance to control (unmanageability) were related to both total and internalizing behavior problems, whereas only difficultness and resistance to control were associated with externalizing behaviors [14]. Although temperament was shown to be predictive of behavior at the time of seizure onset, it is unclear whether it remains predictive years after seizures have developed.…”
mentioning
confidence: 84%
“…To reduce the number of predictors in each model, only two temperament subscale variables were used in each model. These variables were identified based upon theoretical considerations and previous research describing their association with specific behavioral outcomes [14]. For internalizing problems, difficultness and unadaptability were the temperament variables entered, whereas for externalizing problems, difficultness and resistance to control were included.…”
Section: Methodsmentioning
confidence: 99%
“…This sample has been the subject of other reports. [23][24][25][26][27][28] There is no overlap in analyses or results.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] Behavioural disorders are associated with early onset of seizures, 11 certain seizure types, 11 increased seizure frequency, 7,11 polytherapy, 12 cognitive impairment, 3 family factors, parenting practices, and infant temperament. [13][14][15] There are limited data on the prevalence and nature of behavioural problems in children with epilepsy in low-income countries. Two studies from India found similar rates of behavioural (54%) and psychiatric disorders (23%) to those reported from high-income countries.…”
mentioning
confidence: 99%